Ethics and Authenticity in the Age of Virtual Influencers: A Cross-Cultural Review of Consumer Trust and Engagement - Abbastian, Albar Bujayromi (Generate Digital Publishing, 2025)
Objective: This study aims to analyze the key factors that influence consumer trust and engagement with virtual influencers (VIs) through a systematic literature review. Research Design & Methods: This study uses the Systematic Literature Review (SLR) method by examining reputable international journal articles published between 2019 and 2025, focusing on authenticity, transparency, anthropomorphism, and cultural and generational context. Findings: The results show that consistent digital authenticity, balanced disclosure, appropriate human-likeness, and cultural tailoring are the main determinants of VI effectiveness. Risks such as the uncanny valley and consumer skepticism can be minimized with a coherent and transparent digital identity strategy. Implications & Recommendations: Brands need to balance aesthetics and transparency, tailor VI design to demographic and cultural preferences, and ensure narrative coherence to build sustainable engagement. Contribution & Value Added: This study provides a comprehensive conceptual framework on the role of authenticity, disclosure, anthropomorphism, and cross-cultural factors in shaping consumer trust, and offers practical insights for brands in optimizing VI-based marketing strategies.